RETRACTED: A DESCRIPTIVE SURVEY ON SMARTPHONES FEATURES FOR SUPPORTING THE ACADEMIC ACTIVITIES AT UNIVERSITAS PENDIDIKAN GANESHA - Nyoman Putri Rustrini; I Ketut Resika Arthana; Gede Saindra Santyadiputra (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “A Descriptive Survey on Smartphones Features for Supporting the Academic Activities at Universitas Pendidikan Ganesha”, Vol 23, No 2, pp. 200-209, October 2016DOI: http://dx.doi.org/10.21831/jptk.v23i2.13188This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika (KARMAPATI) ISSN: 2252-9063, Vol. 4, No. 5, 2015.The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.